Ionised calcium levels in major trauma patients who received blood in the Emergency Department. Issue 8 (4th February 2016) - Webster, Stacey; Todd, Samuel; Redhead, Julian; Wright, Chris
Abstract : Background: Exsanguination and coagulopathy remain one of the leading causes of preventable trauma related death. Low ionised calcium levels have been associated with hypotension and increased mortality and may inhibit clot formation. Blood product contains citrate that acts as a chelating agent. We hypothesised that trauma patients who have bled are at risk of hypocalcaemia and that receiving any amount of blood product can exacerbate this state. Methods: A retrospective cohort analysis was performed on all trauma patients who had received early blood product in the ED of a single urban major trauma centre in the UK between 2013 and 2014. Ionised calcium levels were taken from venous blood gases from before and after blood product had been transfused. Results: The study included 55 patients; 36 male (65%), age 33 (16–92) years, median injury severity score (ISS) 24 (4–50), units of blood product received 2 (1–16), overall mortality 18%. Fifty-five per cent patients were hypocalcaemic on arrival, 89% patients were hypocalcaemic after receiving any amount of blood product. There was a statistically significant difference in ionised calcium levels after receiving blood product, pretransfusion 1.11 mmol/L (95% CI 1.09 to 1.14), post-transfusion 0.98 mmol/L (95% CI 0.93 to 1.02) (p<0.001). A fall in calcium was seen after receiving just one unit and the more units of blood product received the greater the fall seen. Conclusions: Trauma patients that have sustained blood loss are at risk of hypocalcaemia. Ionised calcium levels fall significantly further even after receiving a small amount of blood product. Prompt recognition and early targeted treatment is needed from arrival.